(untitled) (Journal of Parents and Teachers, 2018)
The two key areas where forgiveness is learnt are revised in this article: Family and School. Special attention is paid to the comprehension of the forgiveness concept, its facilitators and the role of religiosity/spirituality in it. The benefits of forgiveness are highlighted. Finally programs that help in achieving forgiveness are proposed.